1997
DOI: 10.1074/jbc.272.13.8824
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Spread on Immobilized Fibrin Monomer by Mobilizing a β1-class Integrin, Together with a Vitronectin Receptor αvβ3 on Their Surface

Abstract: Human and murine fibroblasts were found to spread far more avidly on fibrin monomer monolayers than on immobilized fibrinogen, indicating that removal of fibrinopeptides by thrombin is a prerequisite for the fibrin-mediated augmentation of cell spreading. In fact, cell spreading was not efficiently augmented on monolayers of a thrombin-treated dysfibrinogen lacking the release of fibrinopeptide A due to an A␣ Arg-16 3 Cys substitution. Since a synthetic Arg-Gly-Asp (RGD)-containing peptide inhibited the fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…43 Staining for a V b 3 integrin (Fig. 7e, f), a fibrin-binding receptor, 44 was also detected. Chondrocytes within articular cartilage stain positively for a 1 b 1 but not for a V b 3 integrin (Fig.…”
Section: Evaluation Of Ecm-chondrocyte Interactionsmentioning
confidence: 95%
“…43 Staining for a V b 3 integrin (Fig. 7e, f), a fibrin-binding receptor, 44 was also detected. Chondrocytes within articular cartilage stain positively for a 1 b 1 but not for a V b 3 integrin (Fig.…”
Section: Evaluation Of Ecm-chondrocyte Interactionsmentioning
confidence: 95%
“…Previous studies have demonstrated that ␣ 5 ␤ 1 binds ligands mainly through the RGD-dependent specificity (45), and the RGD-inhibitable binding of Fg to ␣ 5 ␤ 1 on endothelial cells has been shown (46). ␣ 5 ␤ 1 on other cells has also been reported to bind Fg (47)(48)(49). However, the role of ␣ 5 ␤ 1 in platelet adhesive reactions with Fg is not clear, since this integrin is present on the platelet surface at a considerably lower density than ␣ IIb ␤ 3 .…”
Section: Figmentioning
confidence: 99%
“…16 Briefly, microtiter plates (96-well) were coated with 50 µl of various concentrations (A280 ϭ 0.2) of ascites from the patients with EPS (EPS ascites), and the patient with minimal change nephrotic syndrome, in 50 mM Tris-HCl (pH 7.4), containing 0.135 M NaCl (TBS) at 4°C overnight. After the wells had been washed with TBS, followed by blocking with TBS containing 3% BSA (3% BSA-TBS), 5 ϫ 10 3 human fibroblast cells (TIG-3) were pipetted into the coated wells.…”
Section: Fibroblast Spreading Assaymentioning
confidence: 99%